2021
DOI: 10.3390/telecom2020011
|View full text |Cite
|
Sign up to set email alerts
|

Error Performance Estimation of Modulated Retroreflective Transdermal Optical Wireless Links with Diversity under Generalized Pointing Errors

Abstract: Recent developments in both optical wireless communication (OWC) systems and implanted medical devices (IMDs) have introduced transdermal optical wireless (TOW) technology as a viable candidate for extremely high-speed in-body to out-of-body wireless data transmissions, which are growing in demand for many vital biomedical applications, including telemetry with medical implants, health monitoring, neural recording and prostheses. Nevertheless, this emerging communication modality is primarily hindered by skin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
(121 reference statements)
0
8
0
Order By: Relevance
“…The authors in [5] utilized a continuous wave laser operating at 854.52 nm with a low transmit power of 2.9 mW along with an electro absorption modulator at the retroreflector side and a 4 cm 2 skin sample of a 10 months old laboratory rat to prove the feasibility of established real retro-reflective TOW links. The authors of [144,145], for a power spectral density of 1 µW/MHz, presented encouraging ABER results of 10 −5 to 10 −4 for a reasonable use of wavelength and spatial diversity configurations. Bearing in mind that the most demanding medical applications with IMDs require a signal power density spectrum from 1 µW/MHz to 20 µW/MHz, the authors in [145] showed that over this power density spectrum region, they achieved the proper average SNR values, which were required to drastically address the major effects that degrade TOW performance.…”
Section: Transdermal Optical Wireless Communicationmentioning
confidence: 92%
See 1 more Smart Citation
“…The authors in [5] utilized a continuous wave laser operating at 854.52 nm with a low transmit power of 2.9 mW along with an electro absorption modulator at the retroreflector side and a 4 cm 2 skin sample of a 10 months old laboratory rat to prove the feasibility of established real retro-reflective TOW links. The authors of [144,145], for a power spectral density of 1 µW/MHz, presented encouraging ABER results of 10 −5 to 10 −4 for a reasonable use of wavelength and spatial diversity configurations. Bearing in mind that the most demanding medical applications with IMDs require a signal power density spectrum from 1 µW/MHz to 20 µW/MHz, the authors in [145] showed that over this power density spectrum region, they achieved the proper average SNR values, which were required to drastically address the major effects that degrade TOW performance.…”
Section: Transdermal Optical Wireless Communicationmentioning
confidence: 92%
“…The authors of [144,145], for a power spectral density of 1 µW/MHz, presented encouraging ABER results of 10 −5 to 10 −4 for a reasonable use of wavelength and spatial diversity configurations. Bearing in mind that the most demanding medical applications with IMDs require a signal power density spectrum from 1 µW/MHz to 20 µW/MHz, the authors in [145] showed that over this power density spectrum region, they achieved the proper average SNR values, which were required to drastically address the major effects that degrade TOW performance. Additional experimental work is needed for retro-reflective TOW systems in order to play a key role in energy-efficient wireless telemetry with medical implants.…”
Section: Transdermal Optical Wireless Communicationmentioning
confidence: 92%
“…Accurate pointing error process is modeled by nonzero stochastic model which is composed of two components known as the boresight and jitter. The boresight component represents a fixed displacement between the beam and the detector center, while the jitter is the beam center random offset at the detector plane [5], [15], [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In TOWs, the direct model and modulator retroreflective (MRR) are usually used to configure the transdermal optical link [19][20][21]. In the direct configuration, the external unit acts as the transmitter in order to convey the external modulated stimulated signal through the skin to the implanted unit to produce the proper stimulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation